Stokvels and Intra-Community Ethnic Associations in (Yaoundé) -Cameroon: Harbingers of Stability, Nation-Building and Development - Balon, Sharila Shuka (Advances in Social Sciences Research Journal, 2022)
This article counters the assertion that ethnicization and ethnophobia is a cause of conflict with insights from how ethnic groupings around stokvels and cultural associations help entrench political stability and accelerate rural development where governments and service delivery is in short supply. Drawing from the current geopolitical and regional conflicts splitting former English and French trust territories that have since 1972 united to become one Cameroon, the article argues that, while at its inception the government’s revision of the federal system established in the negotiated 1961 constitution, the former British trust territories of the North and South West regions of present Cameroon have remained glued around ethnic groups and co-existed until the evident and admitted attempts by the government to erode the English Common Law and Anglo-Saxon educational systems. As such a cursory of literature which suggests that ethnicization is a trigger of intractable conflicts is examined with the view of demonstrating that in present-day Cameroon, the ethnicization which has kept a fragile nation together for years is once again the harbingers upon which the country’s stability, nation-building and development is reliant. Using ‘Social Cohesion’ as a reflexive praxis upon which societies are believed to stay together, the article confronts the notion that social cohesion has to be large societal demographics and with the aid of quantitative data sourced from assessing the impact of certain stokvels and intra-community ethnic associations, concludes that, ethnicization is a potent vehicle of stability and development.